A new species of Caridina H. Milne Edwards, 1837 (Family: Atyidae) from a limestone cave on Interview Island, Andaman and Nicobar Islands, India - Vijayamma, Jayachandran Kunjuraman; Dhamorikar, Amruta; Manchi, Shirish (Zootaxa, 2021)
Caridina ravisankarani sp. nov. is a cave-adapted species, collected during June and November 2018 and January 2019 from a limestone cave (CN2) on Interview Island, Andaman and Nicobar Islands. The shrimps were collected from a stream, sourced through the percolation of rainwater, which reduces during the post-monsoon months. The species is closely related to Caridina typus H. Milne Edwards, 1837, Caridina villadolidi Blanco, 1939 and Caridina jeani Cai, 2010. A detailed comparison of characters and a key for identification are given in the text. The present species can be diagnosed by the presence of: short rostum with edentulous upper margin and ventral margin with 2 minute teeth situated at the distal part; outer antennular flagellum with 16 segments at the basal part swollen; highly atrophied propodus and dactylus of endopod of 2nd maxilliped; bushy long setae on fingers of 2nd chelate legs; dactylus of 5th pereopod with 42–43 comb-like bristles; dieresis with 18 spines; dorsal surface of telson with 4–5 pairs of spines and disto-median region doesn’t end in a point, outer lateral pair of spines absent and eyes with cornea pigmentation variable, from totally absent to a small black spot. Fecundity is 1300 eggs with an average length 0.71±0.03 mm and width 0.42±0.03 mm (Mean±SD).